A case of degenerated cervical fibroid polyp - Bhavanam, Nandini; Munisamaiah, Munikrishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Cervical fibroids are often solitary. It may be either interstitial, subserous, submucous or polypoidal. Cervical fibroid usually develops in the wall of the cervix, supravaginal portion. They can change the shape of the cervix or lengthen it, grow rapidly and obstruct the cervix. As fibroids enlarge they may outgrow their own blood supply leading to various types of degeneration. Cystic degeneration is observed in 4% is considered an extreme sequelae of oedema. However atypical appearances that follow degenerative changes can cause diagnostic confusion. Hence misdiagnosis of adenomyoma, hematometra, pyometra, uterine sarcoma and ovarian masses is common.